Beginning MicroPython with the Raspberry Pi Pico build electronics and IoT projects - Bell, Charles (Apress, 2022)
Program the Raspberry Pi Pico, the latest microcontroller board from raspberrypi.org, with MicroPython. This book will take you on a tour of the Raspberry Pi Pico, including how to get started using the microcontroller, seeing which alternative microcontrollers are available, and how to connect and run simple code examples. You'll program example projects in MicroPython using Python on your PC as a learning platform. Then build your hardware skillset working with electronics and breadboard circuits. You'll implement example projects with all steps explained, including hardware connections and executing the project. Then apply them to real-world, approachable projects using the accessible Raspberry Pi Pico! The book shows how the cloud is used for IoT data and find out what popular cloud systems currently exist for IoT. Finally, you'll use ThingSpeak for hosting IoT data including connecting your Pico to the Internet. Beginning MicroPython with the Raspberry Pi Pico allows you to build up your skills to more advanced IoT projects and Cloud systems! What You Will Learn Build valuable programming skills with MicroPython Explore the Raspberry Pi Pico and similar boards Develop your own electronics and IOT projects Incorporate the Grove component system with the Raspberry Pi Pico Who This Book Is For Beginners interested in learning to work with the Raspberry Pi Pico using MicroPython on microcontrollers with little to no experience in programming, hardware, or electronics. The book should also appeal to those who wanting to gain experience with building electronic solutions with microcontrollers.